PENGARUH SOCIAL MEDIA MARKETING TIKTOK TERHADAP MINAT BELI KONSUMEN PADA PRODUK SCARLETT WHITENING - Bessie, Juita L. D.; Wie, Windi Efrinda (Journal of Management Small and Medium Enterprises (SMEs), 2024)
This study aims to determine and analyze: (1) The effect of Entertainment, Interaction, Trendiness, Customization, and e-WOM has a partial effect on Consumer Buying Interest in Scarlett Whitening products. (2) The effect of Entertainment, Interaction, Trendiness, Customization, and e-WOM simultaneously affects Consumer Buying Interest in Scarlett Whitening products. The number of samples is 50 respondents, and the sampling technique used was purposive. The data is collected using Google form questionnaires. The analysis techniques used are quantitative descriptive, Multiple Linear Regression Analysis, and hypothesis testing through t-test and F-test, using the SPSS 22 application. The results of the descriptive analysis show that overall respondents gave a high category perception assessment of Entertainment, Interaction, Trendiness, and Customization and a very high category perception assessment of e-WOM. The results of the t-test and F-test show that partially and simultaneously, Entertainment, Interaction, Trendiness, Customization, and e-WOM have a significant effect on Consumer Buying Interest. Based on the value of Adjusted R2 the contribution of the variables Entertainment, Interaction, Trendiness, Customization, and e-WOM toward Consumer Buying Interest are 97.2%. While 2.8% was influenced by other variables outside the focus of this study. Keywords: Entertainment; Interaction; Trendiness; Customization; e-WOM; Consumer Buying Interest